Penerapan Metode Weight Product (WP) Untuk Menentukan Pengalokasian Pendistribusian Telur Terbaik Di Kecamatan Pantai Labu - Prawita Ardella; Paska Marto Hasugian (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Distribution is an important thing in business activities, especially for distribution companies or distributors. Delays in distribution will reduce customer service levels. The method used is WP (Weighted Product), because Weighted product is one of the right choice of method to solve complex problems and Weighted Product can produce structured calculations on problems that have sub-sub-criteria for the decision to be built. from this research is to determine the best egg distribution location in the pumpkin beach district using the Weighted Product (WP) method. The Weighted Product (WP) method is a multi-criteria analysis decision and is a multi-criteria decision-making method. WP is a set of alternative decisions described in terms of several criteria. In the WP method there is no need for matrix manipulation because this method multiplies the assessment results of each attribute. The results of the research are based on the results of the ranking using the Weighted Product (WP) method to determine the best distribution location in the pumpkin beach district, so the greatest value is Grosir 2 with a value of 0.2309 which can be chosen to be the best distribution location. weights so that they can be used with that method.